Switching probability sub-distributions and asymmetric magnetization reversal in FePt nanostructures - L Herrera Diez; A Bernand-Mantel; L Ranno; D Givord; L Vila; P Warin; A Marty (New Journal of Physics, 2012)
The coercive field statistics in FePt nanostructures reveals the existence of multiple switching probability sub-distributions that can be asymmetric with respect to the field orientation. Each sub-distribution is correlated with an individual magnetization reversal path whose selection cannot happen at the magnetization reversal in negative (positive) field but rather at the moment of applying the initial positive (negative) magnetic field. This serves to determine the reference magnetic state from which reversal in negative (positive) field will develop. The disappearance of the asymmetric sub-distributions upon increasing the initial magnetic field μ _0 H _max supports this model. However, the sub-distributions remaining at high μ _0 H _max are not necessarily those characterized by the highest coercive field. This is attributed to the fact that the initial magnetization state hierarchy and the coercive field hierarchy are essentially decorrelated.